Social Engineering of the Internet in Developing Areas - Wesley Shrum
Communication among researchers is fundamental to the development of knowledge in both developed and developing areas. Internet connectivity is now a precondition for participation in research communication. Establishing reliable and efficient connectivity at reasonable bandwidth is a task that is assumed to be relatively easy and straightforward in developed countries, but is surprisingly difficult in developing areas. Our project has sought to establish connectivity for university departments and government research institutes in India, Ghana, and Kenya but has yet to experience an unqualified 'success' for a variety of institutional and relational reasons. The concept of 'reagency' is used in preference to 'development' to explain the priority of personal relations introducing significant constraints that must be faced directly to establish connectivity in developing areas.